Stanje in razvoj kompetenc zaposlenih v lesni proizvodnji - Jože Kropivšek (Slovenian Forestry Institute, 2016)
The great changes in business environment, rapid technological development and different approaches to work execution demand from employees in industry, including woodworking, to constantly develop their capabilities and widen their knowledge. Education and training are key parts of development of each employee, through which he can gain new knowledge. It is the key to ensuring their competencies for the job, which in turn leads to greater competitiveness of the companies. The objective of the research was to assess the level of competencies for different profiles of employees in wood industry production and to determine the effect of systematic training on the reduction of deficits in competencies. We have established that the biggest deficits in competencies prior to training were in the fields of development, quality management and control, use of computer tools and programming and management of CNC technologies. It can be concluded that the state of competencies of production workers in wood industry is good. Particularly notable is the positive effect of systematic training on the improvement of their competencies, as there was a significant progress of almost all competencies (by 51.8% on average).